2021
DOI: 10.1038/s41550-021-01302-6
|View full text |Cite
|
Sign up to set email alerts
|

HXMT identification of a non-thermal X-ray burst from SGR J1935+2154 and with FRB 200428

Abstract: Identification of a non-thermal X-ray burst with the Galactic magnetar SGR J1935+2154 and a fast radio burst using

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
157
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(166 citation statements)
references
References 40 publications
9
157
0
Order By: Relevance
“…The local nature makes measurements of the object and its environment much easier and with much greater detail. In fact, a linkage between the production of soft gamma bursts in this source and FRBs is naturally suggested: the same two events as the FRBs, with the appropriate delay due to dispersion by interstellar electrons, were detected by γray instruments [24][25][26][27][28] (though some authors suggest that different source types may be responsible for these vs extragalactic FRBs [29]).…”
Section: Application To Sgr1935 + 2154mentioning
confidence: 99%
“…The local nature makes measurements of the object and its environment much easier and with much greater detail. In fact, a linkage between the production of soft gamma bursts in this source and FRBs is naturally suggested: the same two events as the FRBs, with the appropriate delay due to dispersion by interstellar electrons, were detected by γray instruments [24][25][26][27][28] (though some authors suggest that different source types may be responsible for these vs extragalactic FRBs [29]).…”
Section: Application To Sgr1935 + 2154mentioning
confidence: 99%
“…Assuming the same spectral parameters as observed in the FRB 200428associated X-ray burst (ref. 6 ), the 1 s 3σ upper limit of the energy flux in the 8-200 keV band from Fermi/GBM data is 8.1 × 10 −8 erg cm −2 s −1 , and the upper limits from GECAM and Insight-HXMT data are 4.2 × 10 −8 erg cm −2 s −1 (15-200 keV) and 1.8 × 10 −8 erg cm −2 s −1 (200-3000 keV), respectively. Accordingly, the ratio between the luminosity in radio and γ-ray bands, L radio /L γ , is constrained at ≥ 1.4 × 10 −7 (8-200 keV), and ≥ 6.3 × 10 −7 (200-3000 keV).…”
Section: Simultaneous High-energy Observationsmentioning
confidence: 99%
“…Fast radio bursts (FRBs) are highly dispersed radio bursts prevailing in the universe [1][2][3] . The recent detection of FRB 200428 from a Galactic magnetar [4][5][6][7][8] suggested that at least some FRBs originate from magnetars, but it is unclear whether the majority of cosmological FRBs, especially the actively repeating ones, are produced from the magnetar channel. Here we report the detection of 1863 polarised bursts from the repeating source FRB 20201124A 9 during a dedicated radio observational campaign of Five-hundred-meter Aperture Spherical radio Telescope (FAST).…”
mentioning
confidence: 99%
“…It is also shown that the X-ray bursts overlapping the double-peaked CHIME radio burst have an unusually hard spectrum, and it is suggested that these X-rays and the radio bursts arise from a common scenario [15]. Furthermore, the non-thermal nature of the Insight-HXMT burst [19] points to the production of multi-TeV electrons. Multi-GeV to TeV gamma-ray emission via the inverse-Compton process may then accompany this X-ray emission.…”
Section: Introductionmentioning
confidence: 99%